Rehousing Good Citizens: Gender, Class, and Family Ideals in the St. John’s Housing Authority Survey of the Inner City of St. John’s, 1951 and 1952 - Knott, Christine; Phyne, John (Acadiensis)

(untitled) (The Department of History of the University of New Brunswick, 2018)
This article investigates how gendered middle class family ideals were used to relocate administratively defined “good citizens” from a multidimensional yet often demonized “slum” neighbourhood in St. John’s in the 1950s and 1960s. We argue that under the guise of urban renewal, notions of “good citizens” and “good families” were reconstructed along gendered and class lines through housing eligibility criteria for new subsidized housing projects. Our findings show how housing eligibility criteria initially rehoused only specific families from the inner city area. We conclude by discussing the implications of urban renewal in St. John’s for historical work on modernity and on slum clearance.